Comparison of bispectral index and phase lag entropy during general anesthesia: Sevoflurane or propofol anesthesia. Issue 44 (4th November 2022) - Yoo, Jae Hwa; Ok, Si Young; Kim, Sang Ho; Chung, Ji Won; Park, Sun Young; Kim, Mun Gyu; Cho, Ho Bum; Song, Sang Hoon; Choi, Sang Jin; Oh, Hong Chul
Abstract : Background: Phase-lag entropy (PLE) based on functional connectivity between different regions of the brain may be superior to conventional depth of anesthesia (DoA) methods for monitoring changes in consciousness. However, few studies have compared the PLE and bispectral index (BIS) methods for monitoring consciousness during clinical anesthesia, such as total intravenous anesthesia (TIVA) or anesthesia via inhalation. Therefore, we evaluated differences between the PLE and BIS methods in clinical anesthesia, including TIVA using propofol and anesthesia with sevoflurane. Methods: The observational trial included 60 patients scheduled for elective surgery under general anesthesia. The BIS and PLE electrodes were placed together on the left temporal-frontal area of all patients. During anesthesia, anesthetic levels were adjusted using the BIS values, which are generally used to monitor the DoA; the level of anesthesia was maintained at between 40 and 60. BIS- and PLE-derived values were recorded continuously. Anesthetic events, the concentration of each anesthetic, and standard monitoring values were recorded. The patients included were divided into 2 groups, the TIVA and sevoflurane groups, with 30 patients in each. For the TIVA group, anesthesia was induced and maintained using propofol and remifentanil target-controlled infusion. For the sevoflurane group, anesthesia was induced using propofol and maintained using sevoflurane and remifentanil. Results: From loss of consciousness until the anesthetic maintenance period, PLE values were higher than BIS values at several time points. During the recovery period, BIS values were higher than PLE values (all P < .001). Spaghetti plots showed that there was more variation among the BIS values than among the PLE values. Conclusions: For monitoring DoA during general anesthesia and surgery, PLE values vary less than BIS values; thus, PLE may be more reliable for monitoring changes in consciousness. However, further studies are needed to evaluate the clinical application of these methods in general anesthesia.